2016
DOI: 10.1248/bpb.b16-00420
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects of Oligostilbenoids from the Bark of <i>Shorea roxburghii</i> on Malignant Melanoma Cell Growth: Implications for Novel Topical Anticancer Candidates

Abstract: Human malignant melanomas remain associated with dismal prognosis due to their resistance to apoptosis and chemotherapy. There is growing interest in plant oligostilbenoids owing to their pleiotropic biological activities, including anti-inflammatory, antioxidant, and anticancer effects. Recent studies have demonstrated that resveratrol, a well-known stilbenoid from red wine, exhibits cell cycle-disrupting and apoptosis-inducing activities on melanoma cells. The objective of our study was to evaluate the anti-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 28 publications
1
27
0
2
Order By: Relevance
“…Hopeaphenol inhibits topoisomerase IIA and MOS1 transposase . In in vitro studies, this compound inhibited the growth of SK‐MEL‐28 melanoma cells, D‐GBM glioblastoma cells, P‐388 leukemia cells, and the epidermoid carcinoma line KB . In a mouse study, hopeaphenol significantly attenuated tumor formation by sarcoma S‐180 cells that had been subcutaneously allografted into DDY mice.…”
Section: Hopeaphenolmentioning
confidence: 77%
“…Hopeaphenol inhibits topoisomerase IIA and MOS1 transposase . In in vitro studies, this compound inhibited the growth of SK‐MEL‐28 melanoma cells, D‐GBM glioblastoma cells, P‐388 leukemia cells, and the epidermoid carcinoma line KB . In a mouse study, hopeaphenol significantly attenuated tumor formation by sarcoma S‐180 cells that had been subcutaneously allografted into DDY mice.…”
Section: Hopeaphenolmentioning
confidence: 77%
“…Previous phytochemical investigation showed that the stem back and roots of S. roxburghii are composed of phenolic constituents mainly stilbenoids, oligostilbenoids and dihydroisocoumarins. These compounds have displayed several pharmacological functions including cytotoxic, hepatoprotective, antihyperlipidemic, anticancer, antidiabetogenic, antiproliferative and antioxidant properties . However, to the best of our knowledge, there are no reported studies on the chemical components or pharmacological effects of the leaves of S. roxburghii .…”
Section: Introductionmentioning
confidence: 99%
“…(I) It may also be possible to use general CDK inhibitors (flavopiridol, olomoucine, or R-roscovitine) or (J) selective CDK4/6 inhibitors (abemaciclib [LY2835219], palbociclib [PD0332991], or ribociclib [LEE011]). (K) Finally, the combination of BRaf inhibitors with CDK4/6 inhibitors (e.g., palbociclib and vemurafenib) is currently under clinical trial, with reports that it may overcome acquired resistance to treatment based on anti-BRaf inhibitors alone and may offer greater effectiveness than the sum of each therapy individually (Arioka et al, 2017;Ashford et al, 2014;Costantino et al, 2016;Daveri, Valacchi, Romagnoli, Maellaro, & Maioli, 2015;Diehl, Cheng, Roussel, & Sherr, 1998;Ferreira et al, 2016;Fofaria, Kim, & Srivastava, 2014;Kuang et al, 2018;Lavhale, Kumar, Mishra, & Sitasawad, 2009;Li, Wang, & Yan, 2017;Li et al, 2016;Ma, Liu, Qi, & Zhang, 2014;Malyarenko et al, 2017;Matsuzaki et al, 2008;Moriyama, Moriyama, Ninomiya, Morikawa, & Hayakawa, 2016;Nihal, Ahmad, Mukhtar, & Wood, 2005;Nivelle et al, 2018;Park, 2014;Pratheeshkumar & Kuttan, 2011;Siveen & Kuttan, 2011;Sonoda et al, 2008;Tsubaki et al, 2015;Wang, Zhang, Zhang, & Sanderson, 2013;Wang, Xu, et al, 2013;Yokota et al, 2007;You et al, 2017; Table 1).…”
Section: Yclin D1 a S Ther Apeuti C Targ E T In Mel Anomamentioning
confidence: 99%